Covid-19 and surgery: Challenging issues in the face of new normal – A narrative review (2020)
This review aims to outline the current perspectives of surgery in the COVID 19 pandemic associated with the pitfalls in implementing the emerging guidelines to continue patient care without compromising safety, both from the surgeons’ and the patients’ points of view. The fight between the surgeon and the pandemic will be a dragging one since the post-pandemic infflux of surgical patients coupled with the ‘new normal’ practices to prevent COVID 19 spread requires pertinent resources, well-trained personnel, and co-operation among different departments. Emergency surgeries and cancer care have continued all this while, undoubtedly, with unwanted delays and distress. While we continue to prepare ourselves and work in a whole new environment, surgeons are facing the increased chances of litigations and compromised safety. We review what we have come to understand about safe surgical practices during and after the pandemic and the unanswered questions.